Review of the Merodon natans group with description of a new species, a key to the adults of known species of the natans lineage and first descriptions of some preimaginal stages - Ante Vujić; Tamara Tot; Andrijana Andrić; Jelena Ačanski; Ljiljana Šašić Zorić; Celeste Pérez-Bañón; Andrea Aracil; Sanja Veselić; Maja Arok; Ximo Mengual; André van Eck; Santos Rojo; et al. (Arthropod Systematics & Phylogeny, 2021)
Abstract Merodon natans group (Diptera, Syrphidae) taxa are reviewed using an integrative taxonomic approach combining morphological, morphometric and molecular techniques. The approach substantiates recognition of the three species: M. calcaratus (Fabricius, 1794), M. natans (Fabricius, 1794) and M. pulveris Vujić & Radenković in Radenković et al. 2011, and reveals the existence of a new species, M. makrisi Vujić, Radenković & Tot sp. nov., which is described. It also highlights the existence of a series of natans group populations, especially on some of the Mediterranean islands, in the Levant and in the Afrotropical Region, for which more comprehensive data are required to clarify their status. A key is provided to the natans lineage species currently recognised, and preimaginal stages of some natans-group species are described for the first time. Redescriptions for M. calcaratus and M. natans are provided. A neotype is selected for M. natans. Lectotypes are designated for M. annulatus (Fabricius, 1794) and M. melancholicus (Fabricius, 1794). Merodon annulatus is recognised as a synonym of M. natans.